Peranan Masyarakat Desa Dongko Dalam Mewujudkan Desa Wisata Budaya Bersama Mahasiswa UPN “Veteran” Jawa Timur - Fritta Omea Mellenia; Siska Elina Rahmaningsih; Rafli Yovianto; Muhammad Ilham Muladi Wilopo; Eka Nanda Ravizki (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Dongko Village in Trenggalek Regency has made great strides in developing culture-based village tourism. The expansion of cultural tourism in Dongko's tourist village is the focus of this paper. Dongko Village's turonggo yakso jaranan dance is a highlight of this cultural excursion. Since Pokdarwis's inception, this cultural tourist hamlet has grown immensely, especially in terms of the sophistication of its cultural offerings and the harmony with their natural surroundings. The community of Pokdarwis organizes tourism hotspots that are then managed by the locals. Planning, executing, and overseeing cultural tourist activities in Dongko Village with the help of the Thematic Community Service Program at the MBKM, Faculty of Law, UPN "Veteran" East Java, provides insight into Pokdarwis's true purpose. Dongko Village's identity has been bolstered thanks to the efforts of its residents working together to promote cultural village tourism.